Liquid Phase‐Induced Solid Solution Phase Mechanisms for Highly Stable and Ultrafast Energy Storage. Issue 46 (2nd November 2021) - Huang, Meng; Zhu, Jiexin; Yu, Ruohan; Liu, Yu; Liu, Xiong; Wu, Jinsong; An, Qinyou; Mai, Liqiang
Abstract: Phase transitions induce large changes of the lattice parameters, and thus have negative effects on the electrochemical energy storage of electrode materials. In contrast, solid solution phase energy storage mechanisms can ensure smaller shrinkage/expansion of the structure, and therefore better cyclability and fast reaction kinetics of the electrode materials. In this work, the liquid phase is found to control the energy storage mechanisms of K2.55 Zn3.08 [Fe(CN)6 ]2 ·0.28H2 O (KZnHCF). Via in situ characterization techniques, phase‐transition and a solid solution phase hybrid mechanism with large chemical structural decay are observed in electrolytes with low K + concentration, while only a solid solution phase type with a highly stable structure occurs in 5.0 m  KCF3 SO3 and 3.0 m  KCF3 SO3 + 2.0 m  Zn(CF3 SO3 )2 electrolytes. Consequently, the solid solution phase ionic storage mechanism ensures a high rate capability at 20 A g −1 (capacity retention of 66.6%) and a long cyclability of 10 000 cycles (capacity retention of 93.7%) of the KZnHCF cathode. Abstract : In contrast to solid solution energy phase storage mechanisms, phase transitions have negative effects on the structural stability of electrode materials. By controlling the liquid phase, two‐phase mechanisms can be suppressed, and the solid solution phase energy storage mechanism can ensure the excellent rate performance and an ultralong lifespan of K2.55 Zn3.08 [Fe(CN)6 ]2 ·0.28H2 O (KZnHCF) cathode.